2005
DOI: 10.1093/ageing/afi050
|View full text |Cite
|
Sign up to set email alerts
|

Muscle function and functional ability improves more in community-dwelling older women with a mixed-strength training programme

Abstract: Long-term mixed-strength programmes can improve MF and FA in elderly females, and FA in elderly males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
1
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 27 publications
5
23
1
3
Order By: Relevance
“…Although most studies reported that multicomponent training can help to maintain and improve endurance performance in elderly [2,4,34,35] , no significant increase in 6-min walk test performance was found in the present study. The reasons for this inconsistency might be the differences in methods used to determine aerobic endurance, intensity and the nature of training between the present study and previous studies.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Although most studies reported that multicomponent training can help to maintain and improve endurance performance in elderly [2,4,34,35] , no significant increase in 6-min walk test performance was found in the present study. The reasons for this inconsistency might be the differences in methods used to determine aerobic endurance, intensity and the nature of training between the present study and previous studies.…”
Section: Discussioncontrasting
confidence: 94%
“…The improvements in agility/dynamic balance support the concept that older adults are able to improve their agility and balance by multicomponent training [2,4,30,34] . Probably, these agility/dynamic balance improvements might be related to increased muscular strength observed during the training period.…”
Section: Discussionsupporting
confidence: 61%
“…From this viewpoint, determining the characteristics of the electromyographic reaction time of the foot and examining their time-dependent variation may be important for the understanding of qualitative changes in balance function. Furthermore, as reported in previous studies 5,10,19) , the fact that the influence of aging on balance function involves a decreased muscle contraction velocity due to a decline in muscle strength suggests the possibility of maintaining and improving the balance function of the elderly by strengthening the muscles of the ankle joint. In line with these results, further studies will be conducted to examine the effect of muscle-strengthening approaches on balance function, and to evaluate the changes in central processing under different conditions, such as complicated postural control and various trigger stimuli.…”
Section: Discussionsupporting
confidence: 64%
“…Though muscle strength and balance are considered important in terms of assessing motor functions in elderly people [1][2][3] , at present, there is no specific definition of agility in geriatric medicine and physical therapy. Agility in general is defined in the field of sports science, a combination turning ability, accuracy of motion, and full-body motion [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%